2014
DOI: 10.1002/nau.22705
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of benign prostatic obstruction: Development of a clinical nomogram

Abstract: Aims To develop a nomogram predicting benign prostatic obstruction (BPO). Methods We included in this study 600 men with lower urinary tract symptoms (LUTS) and benign prostatic enlargement (BPE) who underwent standardized pressure flow studies (PFS) between 1996 and 2000. Complete clinical and urodynamic data were available for all patients. Variables assessed in univariate and multivariate logistic regression models consisted of IPSS, PSA, prostate size, maximal urinary flow rate (Qmax) at free flow, residua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
1
17
0
4
Order By: Relevance
“…Although our clinical nomogram targets men with refractory LUTS, its accuracy is comparable to that of the previously published nomogram or predictive model in men with treatment-naïve or common LUTS (73.5%–83.2%) 1127. The predictive model proposed by Kim et al 27 was constructed by a combination of Qmax, PVR volume, and TPV.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Although our clinical nomogram targets men with refractory LUTS, its accuracy is comparable to that of the previously published nomogram or predictive model in men with treatment-naïve or common LUTS (73.5%–83.2%) 1127. The predictive model proposed by Kim et al 27 was constructed by a combination of Qmax, PVR volume, and TPV.…”
Section: Discussionsupporting
confidence: 55%
“…Nevertheless, patient age alone does not reliably influence the prediction of BOO in clinical studies. Recently, De Nunzio et al 24 reported that patient age did not differ statistically with respect to the presence of BOO in men with treatment-naïve LUTS;11 moreover, it was not a predictor of BOO in another cohort. In our cohort with refractory LUTS, the mean age of men with BOO was 66.4 years, higher than that of men without BOO (mean age 65.3 years).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…All patients signed an informed consent and the research protocol was developed in accordance with the Helsinki Declaration and preliminary results on the relation between BWT and BOO have been published by some of the co‐authors of our study in 1998 14 . We performed a retrospective analysis of a prospectively collected database 15–17 …”
Section: Methodsmentioning
confidence: 99%